Effects of Acidic Solution on the One-Step Electrodeposition of Prussian Blue Nanocrystals on Screen-Printed Carbon Electrodes Modified with Magnetite Nanoparticles - Man-Mo Tse; Ya-Ling Su; Shu-Hua Cheng (Chemosensors, 2022)
This study investigated the electrochemical synthesis of Prussian blue (PB) nanocrystals on a screen-printed carbon electrode (SPCE) modified with a thin film of magnetite nanoparticles (nano-Fe3O4) in aqueous mixture solutions of potassium hexacyanoferrate(III) and different kinds of acids. The generated PB nanocrystals exhibited varied voltammetric responses that are highly related to the characteristics and properties of acids in the mixture solution. Interestingly, in the presence of glyphosate as an organic acid, surface magnetite nanoparticles were occluded within electrogenerated Prussian blue nanocubes (PBNC), which are characterized by scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), attenuated total reflection Fourier-transform infrared spectroscopy (ATR-FTIR), and cyclic voltammetry (CV). Furthermore, the possible reaction mechanism for the formation of PBNC is proposed in this study. The obtained PBNC was also evaluated as an electrocatalyst of hydrogen peroxide and applied to the detection of glyphosate.